Las fuentes españolas en materia de obligaciones alimenticias. ¿Hacia un Derecho Internacional Privado extravagante? - Garau Sobrino, Federico F. (CUADERNOS DE DERECHO TRANSNACIONAL, 2011)
The application of the Council Regulation (EC) No. 4/2009 has resulted in a very complex situation of rules for resolving the questions of Private International Law (PIL) relating to maintenance obligations. The application of these rules raises two fundamental problems. The first one is that the determination of the applicable rule depends on the different elements in the maintenance obligation. On the other hand, the contents of some of them are extremely complex and at times unintelligible, in such a way that an extravagant (freaky) and hyperspecialized PIL is created, understandable only to the initiates and completely away from their recipients. The EU should consider what kind of PIL want for the future.